Accuracy of Qibla Direction of the Mosque with the Qibla Shadows and Rashdul Qibla Methods - Putri Rohana, Nada Putri (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2024)
This research aims to find out how accurate the Qibla direction of mosques in Sibolga City is and to find out how the Qibla direction measurement method is used in determining the position of the Qibla direction. The research was conducted using the field research method to find out the maslahah mursalah in the virtue of knowing the Qibla direction and addressing the phenomenon of Qibla shadows and rashdul Qibla. Data collection is done by observation, interview, and documentation of data relevant to the study in this research. From the results of the study, it can be concluded that the accuracy of Qibla direction is seen from how the method of measuring Qibla direction is determined based on the measurement of latitude and longitude of the research location.